Vertical Flow Assay for Inflammatory Biomarkers Based on Nanofluidic Channel Array and SERS Nanotags. Issue 32 (22nd June 2020) - Chen, Ruipeng; Du, Xin; Cui, Yujun; Zhang, Xieyuan; Ge, Qinyu; Dong, Jian; Zhao, Xiangwei
Abstract: There is a great demand for the development of detection assays for inflammation infection diagnosis with high throughput and ultrasensitivity. Herein, a vertical flow assay system with functionalized nanoporous anodic aluminum oxide (AAO) as sensing membrane, and encoded core–shell surface enhanced Raman scattering (SERS) nanotags as labels for multiple inflammatory biomarkers detection is presented. A 2 × 2 test array on the porous AAO is developed and modified with multiple capture antibodies to capture inflammatory biomarkers from samples. Due to the high surface area to volume ratio of the AAO membrane, and its influence on plasmonic coupling, the electromagnetic field of the encoded core–shell SERS nanotags is enhanced. Detection limits of 53.4, 4.72, 48.3, and 7.53 fg mL −1 are realized for C reactive protein, interleukin‐6, serum amyloid A, and procalcitonin, respectively, with a linear dynamic range spanning at least five orders of magnitude. In addition, the proposed method also shows acceptable accuracy and repeatability for the detection of clinical samples. Therefore, this approach is expected to be a powerful point of care testing tool for disease diagnosis in facility limited areas. Abstract : Multiplex and quantitative detection of inflammatory biomarkers is challenging in point of care testing since their concentrations cover a wide range from pg mL −1 to µg mL −1 . Here, a vertical flow assay system with functionalized nanoporous anodic aluminum oxide as sensing membrane and encoded core–shell surface enhanced Raman scattering nanotags as labels is presented for multiple inflammatory biomarkers detection.